The Spatial Characteristics of the Hmong Rural Settlements Landscape in Huayuan County at Western Hunan, China - Long, Lingege; Li, Qingxiang; Gan, Zhenkun (MAJ - Malaysia Architectural Journal, 2025)
Diverse and inclusive cities should prioritize the preservation and development of traditional culture. In China, traditional culture is more concentrated and better preserved in rural areas. As the connection between natural and humanistic systems in traditional culture, the rural settlement landscape is created by inhabitants through daily activities, possessing aesthetic, functional, and environmental values. They contribute to the construction of individual, local, and community identities and can promote local socio-economic development through the heritage process. However, urbanization conflicts between urban and rural spatial concepts and lifestyles have affected rural spaces and culture, with rural settlement landscapes being threatened by neglect and deterioration. Therefore, this paper selects the Hmong rural settlements as the research object, aiming to identify their spatial characteristics and values to recognize, acknowledge, and extend the traditional culture. Huayuan County, as the largest Hmong settlement county in western Hunan, combines the religious beliefs, concepts, and customs of the Hmong with the natural mountains and rivers, constituting a unique settlement landscape with outstanding spiritual value and cultural significance. By typology, morphology, to identify eight elements of settlement landscape space. We derive the distinctive features of the settlement landscape characterized by its adjacency to mountains, valleys, and rivers, its overall layout according to local conditions, and the clever forms of dwelling, and explore the inherent influence of Hmong culture, where are imbued with spirituality, collective social structures prevail, and a romantic and exuberant ethnic character resonates through the landscape space. It emphasizes that rural settlement landscapes are essential for ethnic and regional culture carriers, which could help understand traditional cultures, reconstruct local identities, and identify with rural heritage.